2020
DOI: 10.21203/rs.3.rs-64393/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of the Cytokinin sensor TCSv2 in Arabidopsis and Tomato

Abstract: Background: Hormones are crucial to plant life and development. Being able to follow the plants hormonal response to various stimuli and throughout developmental processes is an important and increasingly widespread tool. The phytohormone cytokinin (CK) has crucial roles in the regulation of plant growth and development. Results: Here we describe a version of the CK sensor Two Component signaling Sensor (TCS), referred to as TCSv2. TCSv2 has a different arrangement of binding motifs when compared to previous T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Compelling evidence shows that cytokinin (CK) is required for SAM activity and FM initiation, and that the interplay of transcription factor regulation and CK signaling controls the size and activity of the shoot apical meristem (Kurakawa et al, 2007; Bartrina et al, 2011; Han et al, 2014). Moreover, a recent report showed that the cytokinin reporter TCSv2 is highly expressed in tomato IM/FM meristems, with a particular high signal in doming meristems (Steiner et al, 2020). In our list of DEGs, we identified several genes involved in CK signaling, namely three CYTOKININ OXIDASEs ( CKXs ), CKX1/2/6 , which degrade bioactive cytokinins, and one type-A ARABIDOPSIS RESPONSE REGULATOR ( ARR ), ARR16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compelling evidence shows that cytokinin (CK) is required for SAM activity and FM initiation, and that the interplay of transcription factor regulation and CK signaling controls the size and activity of the shoot apical meristem (Kurakawa et al, 2007; Bartrina et al, 2011; Han et al, 2014). Moreover, a recent report showed that the cytokinin reporter TCSv2 is highly expressed in tomato IM/FM meristems, with a particular high signal in doming meristems (Steiner et al, 2020). In our list of DEGs, we identified several genes involved in CK signaling, namely three CYTOKININ OXIDASEs ( CKXs ), CKX1/2/6 , which degrade bioactive cytokinins, and one type-A ARABIDOPSIS RESPONSE REGULATOR ( ARR ), ARR16 .…”
Section: Resultsmentioning
confidence: 99%
“…In tomato, the switch from vegetative to transition meristem is accompanied by cell division in the meristem, which results in the doming of the TM. Steiner et al (2020) showed that this doming is accompanied by a high cytokinin signal in the meristem. Because CK is a prominent inducer of cell proliferation (Miller et al, 1955), it can probably positively regulate cell division during SAM maturation to allow doming of the meristem and the transition to flowering.…”
Section: Discussionmentioning
confidence: 99%
“…During leaf development, the young leaf undergoes morphogenesis and reaches the mature, differentiated stage of its development simultaneously with the decline in its morphogenetic potential. Compound leaves of tomato are composed of multiple leaflets, which initiate basipetally from a meristematic region at the leaf margin known as the marginal blastozone (Shani et al, 2010; Hagemann and Gleissberg, 1996; Steiner et al, 2020). The leaf morphogenetic potential is harbored by meristematic cells, which respond to CK and therefore exhibit TCS activation.…”
Section: Discussionmentioning
confidence: 99%
“…The number of leaves was counted by dissecting the shoot under a stereomicroscope and counting all the initiated leaves, starting from P1. Differentiation of the meristem to floral and sympodial follows a predictable pattern in S. lycopersicum M82 (Park et al, 2012; Steiner et al, 2020), and was analyzed microscopically in dissected shoots.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation